2020
DOI: 10.1111/anec.12741
|View full text |Cite
|
Sign up to set email alerts
|

Identification of malignant early repolarization pattern by late QRS activity in high‐resolution magnetocardiography

Abstract: Background The early repolarization pattern (ERP) in electrocardiography (ECG) has been considered as a risk for ventricular fibrillation (VF), but effective methods for identification of malignant ERP are still required. We investigated whether high spatiotemporal resolution 64‐channel magnetocardiography (MCG) would enable distinction between benign and malignant ERPs. Methods Among all 2,636 subjects who received MCG in our facility, we identified 116 subjects (43 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…Iwakami et al 8 aimed to differentiate malignant from benign ER pattern by performing magnetocardiography (MCG) on patients diagnosed with ER pattern resuscitated from VF (ERP‐VF(+)) and another group of patients with ER pattern without any history of VF (ERP‐VF(‐)). The results demonstrated that MCG parameters were remarkably different in the two groups and they concluded that MCG can be a useful technique in distinguishing malignant from benign ER pattern with high sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iwakami et al 8 aimed to differentiate malignant from benign ER pattern by performing magnetocardiography (MCG) on patients diagnosed with ER pattern resuscitated from VF (ERP‐VF(+)) and another group of patients with ER pattern without any history of VF (ERP‐VF(‐)). The results demonstrated that MCG parameters were remarkably different in the two groups and they concluded that MCG can be a useful technique in distinguishing malignant from benign ER pattern with high sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Aiming to improve the noninvasive manners to identify the patients who are susceptible to reentrant ventricular tachycardia, signals averaged ECG (SAECG) has been developed over the recent years, which is a modality to evaluate and detect the occult impairment of ventricular activation 5‐8 …”
Section: Introductionmentioning
confidence: 99%
“…17 MCG may be a suitable tool for measuring LV electrophysiological substrates because of its various advantages, such as high spatial resolution, immunity to the various conductivities of intervening tissues, and effortless non-contact mapping. [18][19][20] We hypothesized that the LV conduction pattern demonstrated by MCG could be used to predict the CRT responders in patients with advanced HF.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed MCG recording methods have been described previously. [17][18][19][20] Briefly, we used a 64-channel MCG system (MC-6400; Hitachi High-Technologies, Tokyo, Japan) with highly sensitive superconducting quantum interference device (SQUID) sensors arranged in an 8×8 matrix with 25-mm pitch and a measurement area of 175 mm×175 mm. The magnetic fields measured were then mathematically transformed into electrical currents in accordance with the standard procedure, and time-domain waveforms of their magnitudes were drawn for each channel.…”
Section: Measurement and Analysis Of Mcgmentioning
confidence: 99%
“…The late field refers to small abnormal deflections at the end of the QRS wave. Studies have found late field parameters extracted from MCG to discriminate post-myocardial infarction (MI) patients who had arrhythmia (ventricular tachycardia (VT)) from those who hadn't [113] and to distinguish patients with early repolarization patterns (ERP, known as a risk factor for ventricular fibrillation (VF)) [121]. Compared to late fields extracted from signal averaged ECG (SAECG), MCG late fields provide more accurate prognosis of VT in post-MI patients [113].…”
Section: A Magnetocardiograpy (Mcg)mentioning
confidence: 99%